Prevalence of Escherichia coli Cervical Colonization in Women in Preterm Labor [16H]. (May 2016) - Williams, Marvin; Maxedon, Amanda; McCloskey, Cindy; Bard, David; Chavez-Bueno, Susana
Abstract : INTRODUCTION: Escherichia coli is the leading cause of septicemia in premature newborns. E. coli is transmitted vertically, however, genitourinary colonization rates in women in preterm labor (PTL) are unknown. Our primary objective was to determine the E. coli cervical colonization rate in PTL. Secondary objectives were to describe the strains' antibiotic susceptibilities and phylogroup classification, and the prevalence of bacterial vaginosis (BV). METHODS: Cervical cultures were prospectively obtained from women in PTL, and analyzed for E. coli . The strains' antibiotic susceptibility was determined by the MicroScan WalkAway plus System, and their phylogenetic group was determined by the updated quadruplex PCR Clermont method. A simultaneous vaginal swab was obtained to determine Nugent scores. RESULTS: From September, 2014, through August, 2015, 37 women were recruited. Mean GA was 32.5 (SD±3.19) weeks. E. coli was isolated in four subjects (10.8%) (95% CI 0.8–20.8). Three strains were susceptible to all antibiotics tested; one was resistant to ampicillin and ampicillin/sulbactam. Their phylogroups were B1, C, E, and F, respectively. N=14 (38%) women had BV, including one of the four colonized with E. coli. CONCLUSION: E. coli colonizes the cervix of women in PTL. Antibiotic resistance was not prevalent. BV was not more common in women colonized by E. coli . Phylogroups that occasionally cause neonatal bacteremia were identified but the traditionally invasive neonatal phylogroups B2 and D were not found. A larger study is needed to determine whether E. coli cervical colonization is a risk factor for neonatal sepsis.